Power Regulator Design Using LM317 for Precise and Efficient Power Management - Budihardja Murtianta; Atyanta Nika Rumaksari (Jurnal Elektronika dan Telekomunikasi, 2024)
The Indonesian government plans to transition its transportation sector to electric vehicles (EVs) by 2025. Achieving this ambitious target will necessitate advancements in power management technologies. Therefore, the government is boosting research on energy efficiency, cutting power dissipation, and enhancing the reliability and lifespan of EV components. This study focuses on designing a power-efficient linear voltage regulator using the LM317, which is essential for EV power management. The regulator employs a voltage comparator to monitor feedback voltage and select the correct input voltage, ensuring efficient and stable output power. We tested the LM317 against the LM338 and LM350 in various setups. The results showed that the LM317 performed better in terms of voltage precision, efficiency, power dissipation, and temperature stability. Moreover, the LM317 achieved 75% efficiency in single-source setups and 85% in multi-source configurations, with a voltage precision of ±0.1%. The system’s ability to dynamically select input sources ensures optimal performance for small-signal EV applications.